2012
DOI: 10.1002/adhm.201200067
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticle‐based H2O2 Responsive Controlled‐Release System Used for Alzheimer's Disease Treatment

Abstract: Metal ions play important roles in amyloid aggregation and neurotoxicity. Metal-ion chelation therapy has been used in clinical trials for Alzheimer's disease (AD) treatment. However, clinical trial studies have shown that long-term use of metal chelator can cause adverse side effect, subacute myelo-optic neuropathy. Nanoparticle engineering processes have become promising approaches for efficiently drugs delivery. A series of modified mesoporous silica nanoparticles (MSNs) using redox, pH, competitive binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 51 publications
1
60
0
1
Order By: Relevance
“…Further, anti-Ab monoclonal antibodies Bapineuzumab, Solanezumab also failed to show neuroprotective effect in phase III clinical trials of AD in turn inducing side effects such as meningoencephalitis, vasogenic edema in patients [118]. Mesoporous silica nanoparticles which selectively release the cargo in response to the augmented levels of H 2 O 2 substantially circumvents strong side effect of long term metal chelator use without affecting healthy metal homeostasis [119]. A robust nanocarrier that can span the blood brain barrier and can encapsulate and release several types of drugs to the brain may substantially reverse the AD symptoms.…”
Section: Preclinical Versus Clinical Studiesmentioning
confidence: 99%
“…Further, anti-Ab monoclonal antibodies Bapineuzumab, Solanezumab also failed to show neuroprotective effect in phase III clinical trials of AD in turn inducing side effects such as meningoencephalitis, vasogenic edema in patients [118]. Mesoporous silica nanoparticles which selectively release the cargo in response to the augmented levels of H 2 O 2 substantially circumvents strong side effect of long term metal chelator use without affecting healthy metal homeostasis [119]. A robust nanocarrier that can span the blood brain barrier and can encapsulate and release several types of drugs to the brain may substantially reverse the AD symptoms.…”
Section: Preclinical Versus Clinical Studiesmentioning
confidence: 99%
“…Geng et al 119 reported a biocompatible and H 2 O 2 -responsive controlled-release system to realize target delivery of Alzheimer's disease therapeutic metal chelator. As illustrated in Figure 10, the system was consisted of a mesoporous nanoparticle functionalized with a derivative of aryl boronic acids by forming stable cyclic esters with the adjacent diols of saccharides.…”
Section: H 2 O 2 -Responsive Drug Deliverymentioning
confidence: 99%
“…This order was consistent with our quantitative thermodynamics results. Recent evidence suggests that amyloid oligomers, which represent intermediates in the fibril formation process, are the main source of cytotoxicity by causing the death of neurons for amyloid pathogenesis, rather than the mature fibrils that accumulate as large aggregates 41,42 . To verify the feasibility of the POMds for AD therapeutic applications, we studied their inhibitory effects on Ab oligomers.…”
mentioning
confidence: 99%
“…The metal-induced oligomer of Ab was prepared by treatment with Cu 2 þ at 37°C for 24 h and determined by a native polyacrylamide gel electrophoresis (PAGE) assay ( Supplementary Fig. 10) 42 . Lane 2 in Supplementary Fig.…”
mentioning
confidence: 99%